PENGARUH KONSENTRASI MUTAGEN SODIUM AZIDA (NaN3) TERHADAP DAYA KECAMBAH DAN KERAGAAN BIBIT PADI GOGO VARIETAS KULIT MANIS GENERASI M-1 - Endang Sri R; Tengku Nurhidayah; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This experiment aims to observe the effect of mutagen concentration of sodium azide to the germination and seedling growth performance of upland rice varieties Kulit Manis generation M-1 and the difference in seedling growth of upland rice varieties in Kulit Manis on the generation M-1 by application Sodium Azide some mutagen concentration. The experiment was conducted in an area behind the of Soil Laboratory, Faculty of Agriculture, University of Riau, from May to July 2015. Research was arranged experimentally using Completely Randomized Design, which consists of 5 treatments concentration of sodium azide (SA), ie (0.0, 0.5, 1.0, 1.5 and 2.0 mM). The mean deviation between treatments tested by Duncan New Multiple Range Test (DNMRT) at the level of 5%. Parameters observed were the first count test, the soil emergence test and the percentage of life seedlings. The result showed that the concentration of Sodium Azide significantly effected on the first count test, the soil emergence test and life seedling percentage. Sodium Azide at the concentration of 2.0 mM produce the first count test, the soil emergence test and the lowest percentage of life seedling.Keywords:Upland rice, Sodium azide, Concentration